Dinâmica Populacional na Região Metropolitana de Goiânia: fluxos e mobilidades - Souza, Johnathan dos Santos de (2016)
The present work had as objective to analyze a population dynamics of the Goiânia metropolitan area (RMG), from the beginning of the decade of 1990 until the first decade of the 21st century, along with the factors of its territorial formation. The data used were extracted from the Demographic Data (1991,2000 and 2010), the Atlas of Human Development 2013 and the Information Technology Department of the Brazilian Public Health Care System (DataSUS). The analyzes showed that the population growth has intensified over the years in the municipalities of the surroundings south, west and east of the metropolis. On the other hand, the distribution is concentrated only in five municipalities, all located around the capital. Regarding migrations, we noticed that most of the migration flows are interstate, with the majority coming from only four Brazilian states. In relation to the migration flows within the RMG, the migration between core and peripheral regions is still the one that stands out. The data also showed that the majority of the population of metropolitan municipalities is made up of migrants, except Goiânia. The pendulum migration was also analyzed, and we noticed that the greater flows of workers and students left / leave the most populous municipalities of the region, demonstrating the high degree of articulation between these and the metropolitan nucleus. And lastly, most of the population is made up of young people, which means that they are part of the economic workforce. Finally, the work contributes to the understanding of one of the elements of metropolitan complexity, as well as providing subsidies for further work, and the formulation of public policies by the public municipal and state managers.